2021
DOI: 10.3389/fpls.2021.725571
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Phytophthora sojae Effector Avr1b With E3 Ubiquitin Ligase GmPUB1 Is Required for Recognition by Soybeans Carrying Phytophthora Resistance Rps1-b and Rps1-k Genes

Abstract: Phytophthora sojae is an oomycete that causes stem and root rot disease in soybean. P. sojae delivers many RxLR effector proteins, including Avr1b, into host cells to promote infection. We show here that Avr1b interacts with the soybean U-box protein, GmPUB1-1, in yeast two-hybrid, pull down, and bimolecular fluorescence complementation (BIFC) assays. GmPUB1-1, and a homeologous copy GmPUB1-2, are induced by infection and encode 403 amino acid proteins with U-Box domains at their N-termini. Non-synonymous muta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 86 publications
(135 reference statements)
1
11
0
Order By: Relevance
“…The mutation in Avr1b C-terminus abolishes the interaction with GmPUB1 and the inhibition of cell death. Silencing of GmPUB1 in soybean cotyledons resulted in loss of recognition by the gene products of Avr1b [72]. Overexpression of GmPUB1 triggers cell death and enhanced resistance to Phytophthora, revealing that GmPUB1 is a positive regulator of effector-triggered immunity, and plays a positive role in the defense against Phytophthora [72].…”
Section: Pub E3 Ligases Are Pivotal Regulators In the Response To Bio...mentioning
confidence: 99%
See 2 more Smart Citations
“…The mutation in Avr1b C-terminus abolishes the interaction with GmPUB1 and the inhibition of cell death. Silencing of GmPUB1 in soybean cotyledons resulted in loss of recognition by the gene products of Avr1b [72]. Overexpression of GmPUB1 triggers cell death and enhanced resistance to Phytophthora, revealing that GmPUB1 is a positive regulator of effector-triggered immunity, and plays a positive role in the defense against Phytophthora [72].…”
Section: Pub E3 Ligases Are Pivotal Regulators In the Response To Bio...mentioning
confidence: 99%
“…Oomycete pathogens such as Phytophthora secrete a repertoire of effectors into host cells to manipulate host immunity and benefit infection, including RxLR effectors Avr1b, Avr1d and Avr1k [72]. Several Phytophthora induced GmPUB proteins can interact with the RxLR effectors.…”
Section: Pub E3 Ligases Are Pivotal Regulators In the Response To Bio...mentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, the management of PRSR is largely dependent on resistant cultivars, having one or more resistance genes. For understanding, pathogen race refers to a pathogen’s ability to cause disease in its host ( Anderson et al, 2010 ); in other words, the pathogen race attacks certain resistance genes ( Dorrance et al, 2016 ), and this kind of resistance is accompanied by several mechanisms including effector-triggered immunity (ETI), where R gene products in the host is recognized (directly/indirectly) by specific pathogen effectors termed avirulence (Avr) proteins ( Li et al, 2021 ). Till now, nine Avr genes of P. sojae have been cloned ( Yang et al, 2019 ).…”
Section: Disease Management Pathogenic Diversity and Potential Geneti...mentioning
confidence: 99%
“…During the single dominant gene resistance mechanism against P. sojae , expressed products of Rps genes interact with those of P. sojae through a gene-for-gene interaction and prevent disease development in plants ( Hartwig et al, 1968 ; Schmitthenner, 1999 ; Burnham et al, 2003 ; Fan et al, 2009 ). There are very few reports explaining the detailed expressed products of Rps genes; Gao et al (2005) mentioned the role of coiled-coil–nucleotide-binding–leucine-rich repeat (CC-NB-LRR)-type proteins in the case of Rps1- k locus ,and Li et al (2021) demonstrated that E3 ligase GmPUB1 protein is required for the interaction of P . sojae effector protein Avr1b with the resistance of Rps1b and Rps1k in soybean.…”
Section: Genetics Of Complete Resistance Versus Partial Resistancementioning
confidence: 99%